The Global Effects of Covid-19-Induced Uncertainty - Giovanni Caggiano; Efrem Castelnuovo; Richard Kima (Center for Economic Studies and ifo Institute (CESifo), 2020)
We estimate a three-variate VAR using proxies of global financial uncertainty, the global financial cycle, and world industrial production to simulate the effects of the jump in financial uncertainty observed in correspondence of the Covid-19 outbreak. We predict the cumulative loss in world output one year after the uncertainty shock due to Covid-19 to be about 14%.
Keywords: C32; E32; 330; Covid-19; financial uncertainty; vector autoregressions; global financial cycle; world industrial production